Evaluation of LIS education in Saudi Arabia: Information science undergraduate program at Imam Abdulrahman Bin Faisal University as a case study - Sahhari, Khulud Ali (International Journal of Innovative Research and Scientific Studies, 2025)
The paper aims to briefly examine the history and development of the Information Science Undergraduate Program offered by Imam Abdulrahman Bin Faisal University to enrich LIS literature in Saudi Arabia. It also aims to assess this LIS program according to the LIS Foundational Knowledge Areas (FKAs) Model provided by the IFLA Guidelines for Professional Library and Information Science (LIS) Education Programmes. In a qualitative study, a case study design was followed to formulate the research steps and answer the questions. For data collection, document analysis was conducted, followed by a focus group with the head of the school and the key members of the program development team. The results of the document analysis and the focus group demonstrated that the courses taught in the LIS program at Imam Abdulrahman Bin Faisal University were distributed across the IFLA’s eight Foundational Knowledge Areas (FKAs). However, the distribution across the eight FKAs was not even, as some areas were heavily covered while others were only slightly recognized by the current LIS curricula. In addition, several FKAs were combined into one or more LIS courses, and a given FKA was covered within or by one course or distributed over several courses. The present study is one of the very few research efforts focusing on the LIS programs in Saudi Arabia; it is also the only known study that examines the LIS program at Imam Abdulrahman Bin Faisal University. Therefore, it has recommendations and implications not only for the examined program but also for researchers and academics interested in LIS education in Saudi Arabia.